2023
DOI: 10.3390/jcdd10020078
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum tRNA-Derived Fragments (tRFs) as Potential Candidates for Diagnosis of Fetal Congenital Heart Disease

Abstract: Background: Congenital heart disease (CHD) is one of the most predominant birth defects that causes infant death worldwide. The timely and successful surgical treatment of CHD on newborns after delivery requires accurate detection and reliable diagnosis during pregnancy. However, there are no biomarkers that can serve as an early diagnostic factor for CHD patients. tRNA-derived fragments (tRFs) have been reported to play an important role in the occurrence and progression of numerous diseases, but their roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Statistical analysis was conducted using either Student’s t-test or one-way ANOVA, with a p-value<0.05 indicating statistical significance. To guarantee the dependability of the findings, the experiments were conducted a minimum of three times ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis was conducted using either Student’s t-test or one-way ANOVA, with a p-value<0.05 indicating statistical significance. To guarantee the dependability of the findings, the experiments were conducted a minimum of three times ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…The volume of osteophytes or bone spurs was quantified to assess the extent of joint damage in knee osteoarthritis. Furthermore, each sample was given a macroscopic rating using a previously documented technique that quantitatively assesses the severity of OA (26).…”
Section: Rat Oa Model and Treatments In Vivomentioning
confidence: 99%
“…tRNA was first thought to be stable, however, recent developments in unbiased high-throughput sequencing facilitated the discovery of a new class of tRNA: tRNA halves (31–40 nucleotides) and tRNA-derived fragments (tRFs, 14–30 nucleotides) ( Cole et al, 2009 ; Lee et al, 2009 ; Liao et al, 2010 ). While our current understanding of the functional role of transfer RNA fragment (tRF) in CHD is still in its infancy, the pioneering study of Lu et al, 2023 has shown that distinct tRNA fragments might serve as a biomarker for accurate diagnosis of CHD during pregnancy. Here, 18 tRFs/tiRNAs were selected as predictive biomarkers of CHDs.…”
Section: Transcriptomes In Congenital Heart Diseasesmentioning
confidence: 99%
“…Here, 18 tRFs/tiRNAs were selected as predictive biomarkers of CHDs. By further analysis, tRF-58:74-Gly-GCC-1 and tiRNA-1:35-Leu-CAG-1-M2 were validated as promising biomarkers of CHD ( Lu et al, 2023 ). The onset and progress of CHD, mainly in early pregnancy, is a complex and relatively long-term process involving many genetic and epigenetic alterations.…”
Section: Transcriptomes In Congenital Heart Diseasesmentioning
confidence: 99%